2016
DOI: 10.1002/anie.201607208
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Catalytic Chiral Leaving Group for Asymmetric Substitutions at sp3‐Hybridized Carbon Atoms: Kinetic Resolution of β‐Amino Alcohols by p‐Methoxybenzylation

Abstract: A catalytic strategy was developed for asymmetric substitution reactions at sp -hybridized carbon atoms by using a chiral alkylating agent generated in situ from trichloroacetimidate and a chiral phosphoric acid. The resulting chiral p-methoxybenzyl phosphate selectively reacts with β-amino alcohols rather than those without a β-NH functionality. The use of an electronically and sterically tuned chiral phosphoric acid enables the kinetic resolution of amino alcohols through p-methoxybenzylation with good enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 62 publications
(19 reference statements)
2
24
0
Order By: Relevance
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…Thus, catalyst 3 was deactivated by this side reaction, although covalently linked phosphate esters were recently reported as an active intermediate in chiral phosphoric acid catalysis. 12 The proposed reaction pathway, which involves the deactivation pathway, was also confirmed by theoretical studies of a model system. These theoretical studies also indicated that the sulfonamide unit introduced to the phosphorus center is the key to accelerating the proposed synchronous anti -S N 2′ reaction through transition state A .…”
Section: Resultsmentioning
confidence: 60%
“…Recently, some examples have emerged indicating that the chiral phosphoric acid undergoes a substitution reaction with the substrate, where the acid catalyst functions as a nucleophile, to generate the corresponding phosphate ester as the reactive intermediate. 12 As depicted in Scheme 4 , in principle, phosphorimidate B , which was generated through the S N 2 reaction of catalyst 3 with 1 at the terminal allylic position far from R group, might be involved as the reactive intermediate in the present reaction. Because the S N 2 reaction, giving B with inversion at the substitution site, followed by the syn -S N 2′ reaction through D , namely, the net anti -S N 2′ pathway, also fulfils the requirement of the experimental evidence obtained in the deuterated substrate experiment as shown in Scheme 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] First, imino phosphonates 5a-c were subjected to an asymmetric Friedel-Crafts-type reactionw ith indole 9a using BINOL-derived chiral phosphoric acid [14] as the asymmetricc atalyst. [15,16] In the presence of BINOL-derived phosphoric acidc atalyst 10 a in toluene, [9] 5a gave adduct 11 aa in good yield with moderate selectivity (63 % ee,e ntry 1). The use of more bulky substrates 5b or 5c improved the stereoselectivity (entries 2a nd 3).…”
Section: Resultsmentioning
confidence: 99%